Polysaccharides from fermented Momordica charantia L. with Lactobacillus plantarum NCU116 ameliorate metabolic disorders and gut microbiota change in obese rats. Issue 6 (26th February 2021) - Wen, Jia-Jia; Li, Ming-Zhi; Gao, He; Hu, Jie-Lun; Nie, Qi-Xing; Chen, Hai-Hong; Zhang, Yan-Li; Xie, Ming-Yong; Nie, Shao-Ping
Abstract : Obesity is a chronic disease characterized by overweight resulting from fat accumulation, along with disturbance of metabolism and gut microbiota. Abstract : Obesity is a chronic disease characterized by overweight resulting from fat accumulation, along with disturbance of metabolism and gut microbiota. Fermentation, as a green processing method, is beneficial for improving the nutrition capacity of food components. Polysaccharides are considered as one of the important components in food and are also potential supplements for anti-obesity treatment. This study aimed to investigate the anti-obesity effects of polysaccharides from fermented and non-fermented Momordica charantia L. with Lactobacillus plantarum NCU116 (FP and NFP) on obese rats by serum metabolomics and gut microbiota analysis. Metabolomics results revealed that abnormal lipid metabolism was formed due to obesity. The supplement of FP and NFP improved the glycerophospholipids, glycosphingolipids, and amino acid metabolism of the obese rats, which alleviated the hypercholesterolemia and overweight in rats. Furthermore, the disorder of gut microbiota was ameliorated by FP and NFP. FP promoted the growth of beneficial bacteria, such as phylum Firmicutes, Actinobacteria, and genera Anaerostipes, Coprococcus, Lactobacillus, and Bifidobacterium . FP also reduced several harmful bacteria belonging to the phylum Proteobacteria and genera Helicobacter . The positive correlation of the weight loss and lowering of serum lipids with the increased beneficial bacteria further elucidated that the anti-obesity effect of FP in obese rats is associated with the regulation of gut microbiota and serum metabolites. The results of this study could provide information for developing probiotic products in the future that may have beneficial effects on the prevention or treatment of obesity.